PENGARUH MANUVER KENDARAAN PARKIR DI BADAN JALAN TERHADAP DERAJAT KEJENUHAN PADA JALAN TEUKU UMAR KOTA BANDA ACEH - Yusmadi Yusmadi; Sugiarto Sugiarto; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Teuku Umar Street has very high activities as an access service, but there are also on-street parking facilities. On-street parking facilities cause traffic congestion on teuku umar road area, especially in public service areas such as Seutui Market, Harapan Bunda Hospital, Suzuya Mall and Canai Mamak. This is caused by the influence of vehicle maneuvers when entering and exiting from parking facility location, and  this phenomenon often occurs during rush hour and the volume of vehicles is very dense. Based on these problems, a study was conducted to determine the effect of vehicle maneuvers when exiting and entering of parking facility on the traffic of degree of saturation and relation model between volume, speed and density using 3 models i.e. Greenshields, Greenberg and Underwood. Based on the analysis results, the Greenberg Model is the best model with the highest determination of the three variables of speed-density-volume. The model is chosen based on the greatest value of determination approaching one rate. The capacity of Teuku Umar Street Directions Gunongan-Sp.Tiga is 2970 pcu/hour, and after the on-street parking activity, the capacity decreased by 2079 pcu/hour (30%). For the way to Gunongan, the capacity is 2970 pcu/hour, after parking activities the capacity drops 2524 pcu/hour (15%). The value of saturation degree in the segment is no parking facility towards Gunongan to Sp. Tiga is 0.31 and there is parking obtained 0.43. Sp. Tiga-Gunongan street direction has the value of surfeit level on the segment no parking facility at 0.37 and there is parking obtained at 0.44. The alternative improvements to increase capacity is by providing special parking facilities and limiting vehicles in and out, so that the surfeit level will decrease.